Parents' Perceptions and Intention to Vaccinate Their Children Against COVID-19: Results From a Cross-Sectional National Survey in India - Padhi, Bijaya Kumar; Satapathy, Prakasini; Rajagopal, Vineeth; Rustagi, Neeti; Vij, Jatina; Jain, Lovely; Chakrapani, Venkatesan; Patro, Binod Kumar; Kar, Sitanshu Sekhar; Singh, Ritesh; Pala, Star; Sankhe, Lalit; et al. (Frontiers in Medicine, 2022)
Background Despite the success of adult vaccination against COVID-19, providing vaccines to children remains a challenge for policymakers globally. As parents are primary decision-makers for their children, we aimed to assess parents perceptions and intentions regarding COVID-19 vaccination in India. Methods A cross-sectional web-based study was designed, parents or caregivers (N=770) were recruited through snowball sampling using Google form. Cross-tabulation was performed by parents intention to vaccinate their children against COVID-19 virus with sociodemographic characteristics and their risk perception towards COVID-19, trust in the healthcare system, and their history of vaccine hesitancy behavior. Multivariable logistic regression analysis was performed to compute the predictors of child vaccination intention among Indian parents. Results Seven hundred seventy parents across the country have completed the survey. Of the 770 participants, 258 (33.5%) have shown intent to vaccinate their children. The stated likelihood of child vaccination was greater among parents who had a bachelors degree or higher education (aOR: 1.98, 95% CI: 1.15-3.51); as well as among parents who intended to vaccinate themselves (aOR: 2.35, 95% CI: 1.30-4.67). Parental concerns centered around vaccine safety and side effects. Conclusion Indian parents reported high knowledge of the COVID-19 virus and were aware of the development of a novel vaccine. However, about one-third of parents intended to vaccinate their children, and about half of them were not sure whether to vaccinate their children or not against the COVID-19 virus. The study highlighted the need for health promotion strategies that promote vaccine uptake among parents.